The impact of personal health literacy and school health literacy environments on schoolteachers' health outcomes - Yu, Mingyang; Liu, Rongmei; Zhao, Qiuping; Wang, Junfang; Bai, Yuxi; Yang, Xiaomo; Liu, Shuaibin; Okan, Orkan; Hua, Bing; Dai, Nengguang; Xu, Suyan; Guo, Shuaijun (Frontiers in Public Health, 2025)
BackgroundThe relationship between personal health literacy and health outcomes is clear, but the role of health literacy environments is often overlooked. This study examined associations between personal health literacy, school health literacy environments and health outcomes among schoolteachers.MethodsA cross-sectional study was conducted among 7,364 schoolteachers in Zhengzhou, China. Personal health literacy was measured by the Health Literacy Population Survey 2019–2021 (excellent/sufficient/problematic/inadequate) and school health literacy environments were measured by the Organisational Health Literacy of School Questionnaire (supportive/less supportive). Health outcomes included health status (poor/good), health-compromising behaviours (yes/no), health service use (yes/no), and healthcare cost (≥RMB 1,000/ <RMB 1,000).ResultsOver half of teachers had inadequate or problematic health literacy. Teachers with inadequate health literacy had higher odds of poor health status, health-compromising behaviour, health service use, and high healthcare cost than those with excellent health literacy. Similarly, teachers who perceived less supportive school health literacy environments had higher odds of poor health outcomes.ConclusionBoth personal health literacy and school health literacy environments are important to schoolteachers' health outcomes. Educational programs and organisational change are needed to improve personal health literacy and school environments to improve schoolteachers' health and wellbeing.